Analysis of Low Lead and Cadmium Concentrations in Soil Extracts by Graphite Furnace Atomic Absorption Spectrophotometry - Jopony, Marcus (Universiti Putra Malaysia Press, 1993)
An analytical procedure was derived to provide an accurate measurement of low lead (Pb) and cadmium (Cd) concentrations in soil extracts using graphite furnace atomic absorption spectrometry (GFAAS). Based on peak area measurements and with background correction, the use of 2% phosphoric acid as chemical modifier enables the GFAAS to give measurements of Pb and Cd concentration as low as 3 fLg dm-3 with a high degree of precision. The modifier ensures a single well-defined atomization peak of the analyte, and therefore higher sensitivity and accuracy in the measurements.